Quantum discord of photon interaction with two two-level atoms under damping - M. Mirzaee
We study quantum discord of the interaction between two two-level atom and photon near resonance under damping. It is shown that quantum discord in absence of damping oscillate with time, while in the presence of damping decrease with time. In this case, it is evidence that there is a transition from quantum correlation to classical correlation. This behavior is similar to the constructions that have been used to show the quantum entanglement is a proper measure of quantum entanglement.
Keywords: Physics; Quantum mechanics, field theories, and special relativity; Optics